Qinghao-Biejia Herb Pair Alleviates Pristane-Induced Lupus-Like Disease and Associated Renal and Aortic Lesions in ApoE−/− Mice - Hong, Jiaze; Zhang, Miao; He, Yuanfang; Jin, Yi; He, Qiaoqi; Zhang, Yi; Shi, Xiaowei; Tian, Weiyu; Wen, Chengping; Chen, Juan (Frontiers in Pharmacology, 2022)
Backgroud: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease involving multiple systems with a high prevalence of nephritis and atherosclerosis. Jieduquyuziyin prescription is a famous prescription with immune modulating and inflammation controlling effects, which is efficacious in the treatment of SLE. The most critical herbs in this prescription are Qinghao and Biejia. The aim of this study was to evaluate the therapeutic effect of Qinghao-Biejia herb hair (QB) on mice with SLE combined with atherosclerosis. Materials and Methods: The effect of QB (identification using UPLC-TOF-MS)was assessed in female ApoE-/- mice intraperitoneally injected with 0.5 ml of pristane. Serum autoantibodies and lipid metabolic parameters were tested every 4 weeks, and spleen index, serum inflammatory biomarkers, renal injury and aortic injury were observed after 16 weeks. The expression of signaling pathway in kidney tissues was observed by RT-qPCR and Western blot. Results: The mice of QB-treated group exhibited a significant reduced serum autoantibodies level, urine protein, and renal immune complex deposition. QB treatment reduced the levels of inflammatory cytokines and improved the renal pathological changes. In addition, there was a reduction in aortic atheromatous plaque and some improvement in dyslipidemia. Moreover, QB suppressed the expression of HMGB1, TLR4 and MyD88 to some extent. Conclusions: The present study implied that QB has clear efficacy for the treatment of SLE combined with atherosclerosis, and that inhibition of the HMGB1/TLR4 signaling pathway may be one of the therapeutic targets of QB for SLE combined with atherosclerosis.